Undaria pinnatifida extract attenuates combined allergic rhinitis and asthma syndrome by the modulation of epithelial cell dysfunction and oxidative stress - Yu Zhen Nan; Fan Yan Jing; Nguyen Thi Van; Piao Chun Hua; Lee Byung-Hoo; Lee So-Young; Shin Hee Soon; Kim Tae-Geum; Song Chang Ho; Chai Ok Hee (Acta Biochimica et Biophysica Sinica)
Undaria pinnatifida ( U. pinnatifida) has long been a part of the human diet and medicine. Although U. pinnatifida has been reported to have immunomodulatory, anti-inflammatory, anti-diabetic and antibacterial activities, its specific effect on patients with combined allergic rhinitis and asthma syndrome (CARAS) has not been clarified. In this study, the anti-allergic and anti-inflammatory effects of U. pinnatifida extract (UPE) are investigated in a mouse model of ovalbumin (OVA)-induced CARAS. The oral administration of UPE inhibits allergic responses by reducing OVA-specific immunoglobulin levels. As a result, the symptoms of early reactions are also improved. UPE inhibits the accumulation of inflammatory cells and attenuates the expression of Th2 cytokines in both nasal and bronchoalveolar lavage fluid. Furthermore, UPE treatment inhibits the NF-κB/MAPK signaling pathway in lung homogenates. Additionally, UPE prevents shedding of the nasal mucosal epithelium, protects the integrity of the epithelium, enhances the expression of E-cadherin at the junction of epithelial cells, and inhibits the degradation of ZO-1 and occludin in the airway epithelium. In addition, UPE ameliorates dysfunction of the nasal epithelial barrier by enhancing antioxidant properties and downregulating the expression of the inflammatory factor IL-33. These results suggest that UPE may treat CARAS by modulating epithelial cell dysfunction and oxidative stress.